One hectare rainfed farming system for food security – A success story - Das, Ashis; Mishra, Ashish; Mishra, Surya Narayan; Nayak, Ansuman (Indian Farming, 2015)
Chaitaram Batra a middle class farmer of block Jharigaon, district Nabarangapur, Orissa holding of 2.5 acre land, who earned his live hood with his family uncomfortably in previous years because of following small scale production systems with low external inputs and traditional varieties. Now due to acceptance of concept of one hectare (2.5 acre) rainfed food security model with proper enterprises and improved variety guided by scientists of Krishi Vigyan Kendra, Nabarangapur, his annual gross income has significantly increased from Rs. 13,300 to Rs. 47,190 which shows his annual profit now is Rs. 29,420 over Rs.6,225 previously, excluding family labour engaged and of around Rs. 5,000 in terms of green vegetable, dal etc which were consumed by his family members.